PERANCANGAN PENGERING GABAH MENGGUNAKAN PEMANAS UDARA DARI TUNGKU SEKAM - Lukas Kano Mangalla (Universitas Halu Oleo, 2008)
After harvesting technology drying process was an important knowledge for a rice farmer. The paddy was usually dried within 6 day in the raining season. In order to solve the problem, a drying technology has been developed by utilizing farm waste, such as husk alternative fuel. The aim of the research is to design an effective and efficient of rice dryer by using energy as result of sekam burned. Dryer scheme use the simple equipments and economically. Frame of dryer construction can be using the log while wall from Plywood. Burned chamber of sekam fuel was made to be separated from dryer space. Heat combustion was transfer to the drier space by a number of small pipes. Evaluated of dryer conducted by filling 3 kg shell of rice into dryer space after sekam begin to burning. Temperatures of each tray dryer’s chamber and external air were measured. Result of research show the device of dryer space by using heater from sekam burned was very effective for rice paddy dryer. Temperature in dryer space can be reached 40oC to 55oC where the temperature was near the maximum temperature reached by direct sun irradiating. Key words: Drier, Combustion, Biomass Energy